Quadruple-arc Gear Form Grinding Wheel cross-section shape design and calculation - Zhao Yi; Ren Zhongyi; Duan Jianzhong (Jixie chuandong, 2016)
One key of quadruple- arc gear form grinding is to calculate the grinding wheel cross- section shape. Firstly,a coordinate system is built depend on form grinding principle. Through the quadruple- arc gear tooth surface equation and gear tooth surfaces in contact with the grinding wheel surface condition,the grinding wheel cross- sectional shape is obtained by using space coordinate transformation. Finally,by using MATLAB software computing and graphics capabilities to calculate and simulate the grinding wheel cross- section shape. The grinding wheel cross- section shape is verified by processing experiment.